The Relationship Between Medical Record Quality and Nursing Care Quality - Ricky Riyanto Iksan riyanto iksan; Amika Rois amika rois; ‎ Meliana; Supriyanto Supriyanto Supriyanto (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
This study aims to analyze the relationship between the quality of medical records and the quality of nursing care in the inpatient ward of a hospital. Method: This study used a quantitative design with a cross-sectional approach. The study sample consisted of 86 patient medical records selected using a purposive sampling technique. The instruments used were medical record quality observation sheets based on the aspects of completeness, accuracy, timeliness, and readability, as well as nursing care quality audit sheets based on nursing process standards (assessment, diagnosis, intervention, implementation, and evaluation). Data analysis was performed using the chi-square test with a significance level of 0.05. Results: The results showed that most medical records were in the good category (62.8%) and the quality of nursing care was also in the good category (65.1%). The results of statistical tests showed a significant relationship between the quality of medical records and the quality of nursing care (p-value = 0.003; p < 0.05). The better the quality of medical records, the better the quality of nursing care provided. Conclusion: There is a significant relationship between the quality of medical records and the quality of nursing care. Improving the quality of medical record documentation can support the improvement of the quality of nursing services. Hospitals are advised to improve supervision and training related to nursing documentation to ensure optimal service quality.